Mimicking Infants' Early Language Experience Does Not Improve Adult Learning Outcomes. Issue 1 (2nd January 2018) - Hudson Kam, Carla L.
ABSTRACT: Adult learners know that language is for communicating and that there are patterns in the language that need to be learned. This affects the way they engage with language input; they search for form-meaning linkages, and this effortful engagement could interfere with their learning, especially for things like grammatical gender that often have at least a partial phonological basis. Children learning their first language do not face this interference initially, which may facilitate the learning of some grammatical patterns. In this study I ask whether learning outcomes could be improved in adults encouraged to engage with input in a more infant-like way. Across five experiments, adults were exposed to a miniature artificial language with grammatical gender-like patterns. Exposure either included both speech and meaning throughout, or initially, just the speech, followed by exposure to both speech and meaning. Sound-only initial exposure did not improve learning outcomes in adult learners.